Cost Analysis of In-Home Telerehabilitation for Post-Knee Arthroplasty - Tousignant, Michel (J Med Internet Res, 2015)
BACKGROUND: Rehabilitation provided through home visits is part of the continuum of care after discharge from hospital following total knee arthroplasty (TKA). As demands for rehabilitation at home are growing and becoming more difficult to meet, in-home telerehabilitation has been proposed as an alternate service delivery method. However, there is a need for robust data concerning both the effectiveness and the cost of dispensing in-home telerehabilitation. OBJECTIVE: The objective of this study was to document, analyze, and compare real costs of two service delivery methods: in-home telerehabilitation and conventional home visits. METHODS: The economic analysis was conducted as part of a multicenter randomized controlled trial (RCT) on telerehabilitation for TKA, and involved data from 197 patients, post-TKA. Twice a week for 8 weeks, participants received supervised physiotherapy via two delivery methods, depending on their study group allocation: in-home telerehabilitation (TELE) and home-visit rehabilitation (VISIT). Patients were recruited from eight hospitals in the province of Quebec, Canada. The TELE group intervention was delivered by videoconferencing over high-speed Internet. The VISIT group received the same intervention at home. Costs related to the delivery of the two services (TELE and VISIT) were calculated. Student’s t tests were used to compare costs per treatment between the two groups. To take distance into account, the two treatment groups were compared within distance strata using two-way analyses of variance (ANOVAs). RESULTS: The mean cost of a single session was Can $93.08 for the VISIT group (SD $35.70) and $80.99 for the TELE group (SD $26.60). When comparing both groups, real total cost analysis showed a cost differential in favor of the TELE group (TELE minus VISIT: -$263, 95% CI -$382 to -$143). However, when the patient’s home was located less than 30 km round-trip from the health care center, the difference in costs between TELE and VISIT treatments was not significant (P=.25, .26, and .11 for the <10, 10-19, and 20-29 km strata, respectively). The cost of TELE treatments was lower than VISIT treatments when the distance was 30 km or more (30-49 km: $81<$103, P=.002; ≥50 km: $90<$152, P<.001). CONCLUSIONS: To our knowledge, this is the first study of the actual costs of in-home telerehabilitation covering all subcosts of telerehabilitation and distance between the health care center and the patient’s home. The cost for a single session of in-home telerehabilitation compared to conventional home-visit rehabilitation was lower or about the same, depending on the distance between the patient’s home and health care center. Under the controlled conditions of an RCT, a favorable cost differential was observed when the patient was more than 30 km from the provider. Stakeholders and program planners can use these data to guide decisions regarding introducing telerehabilitation as a new service in their clinic. TRIAL REGISTRATION: International Standard Registered Clinical Study Number (ISRCTN): 66285945; http://www.isrctn.com/ISRCTN66285945 (Archived by WebCite at http://www.webcitation.org/6WlT2nuX4).